2019
DOI: 10.1080/21691401.2019.1699813
|View full text |Cite
|
Sign up to set email alerts
|

Cytisine exerts anti-tumour effects on lung cancer cells by modulating reactive oxygen species-mediated signalling pathways

Abstract: Jin (2020) Cytisine exerts anti-tumour effects on lung cancer cells by modulating reactive oxygen species-mediated signalling pathways,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 28 publications
(32 reference statements)
1
15
0
Order By: Relevance
“…Our preliminary studies indicated that cytisine was nontoxic not only against normal human fibroblasts (BJ) but also against human squamous cell carcinoma (SCC-15) and U-118 human glioma cells up to 500 µM after 24 h incubation (data not shown). However, an anticancer potential of cytisine against lung cancer cells [36] and HepG2 human hepatocellular carcinoma cells from few micromolar concentrations has been reported [37]. We found that G3 2C16gh and G3 9C11gh conjugates were not toxic up to 200 µM concentration and even stimulated 20% BJ cells growth at 3.1 and 50 µM concentrations, respectively ( Figure 10).…”
Section: Toxicity Of Conjugatesmentioning
confidence: 60%
“…Our preliminary studies indicated that cytisine was nontoxic not only against normal human fibroblasts (BJ) but also against human squamous cell carcinoma (SCC-15) and U-118 human glioma cells up to 500 µM after 24 h incubation (data not shown). However, an anticancer potential of cytisine against lung cancer cells [36] and HepG2 human hepatocellular carcinoma cells from few micromolar concentrations has been reported [37]. We found that G3 2C16gh and G3 9C11gh conjugates were not toxic up to 200 µM concentration and even stimulated 20% BJ cells growth at 3.1 and 50 µM concentrations, respectively ( Figure 10).…”
Section: Toxicity Of Conjugatesmentioning
confidence: 60%
“…Some studies have suggested that targeting the nicotinic acetylcholine receptors holds promise as a new therapeutic approach for the treatment of depression [6]. It was found that cytisine induces the apoptosis of HepG2 cells [7] and has anti-tumor effects on lung cancer cells by modulating reactive oxygen species-mediated signaling pathways [8]. Przybył et al investigated the antiproliferative activities of cytisine derivatives against selected cancer cell lines [9].…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic mitochondrial apoptotic pathway is characterised by alterations in the permeability of mitochondrial membranes [ 30 ]. In the present study, we used JC-1 staining.…”
Section: Discussionmentioning
confidence: 99%